The Philippines: Open Spaces for Catholic Worship - Esteban Fernández-Cobián (Religions)
The Philippines is an island nation in Southeast Asia with a population of approximately 100 million. Its hot and humid climate makes it common for community buildings to be permanently ventilated or even open to the elements. The country’s susceptibility to natural disasters, such as earthquakes, volcanic eruptions, and typhoons, also imparts unique characteristics to its architecture, including its religious buildings. Additionally, apart from tiny East Timor, the Philippines is the only nation in the region where the vast majority of the population professes the Catholic faith. The openness of spaces used for Catholic worship can be understood not only from a climatic standpoint but also as a reflection of the Filipino people’s identity. Historically, they have not confined their faith celebrations to the interior of churches but have instead utilized public spaces for religious expressions, making these spaces a means of communal affirmation of their national identity. This article explores the typology of open religious architecture in the Philippines, examining both the physical connection between indoor and outdoor spaces—highlighting the environmental or climatic factors—and the temporary nature of its construction, which emphasizes the social or identity dimension. By doing so, it reveals the links between form, function, and local culture in the country’s religious architecture.